1961
DOI: 10.1017/s0025315400016222
|View full text |Cite
|
Sign up to set email alerts
|

Biological differences between sea waters: experiments in 1960

Abstract: The experiments during the 1953 season were arranged to investigate certain criticisms and suggestions made to us after publication of the earlier work (Wilson, 1951;Wilson & Armstrong, 1952), and there were included tests of our own devising intended to narrow the field within which must be made any search for an explanation of the observed biological differences between sea waters from different localities. We were again unable to obtain water from the Celtic Sea and once more, by kind co-operationof the Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1963
1963
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has already been reported by many researchers (Waterman 1937, Wilson and Armstrong 1951-1961, Bernhard 1957, Okubo and Okubo 1962, Soyer 1963, Bougis 1961-1967, Hagstrom and Lonning 1973and Heslinga 1976) that the polluted sea water affects the pluteus formation in various sea urchins. Especially, Heslinga (1976) reports that the pluteus process appears to be very sensitive and therefore may be best suited to assess the stress by pollution in Echinometra.…”
Section: I I Considerationsmentioning
confidence: 93%
“…It has already been reported by many researchers (Waterman 1937, Wilson and Armstrong 1951-1961, Bernhard 1957, Okubo and Okubo 1962, Soyer 1963, Bougis 1961-1967, Hagstrom and Lonning 1973and Heslinga 1976) that the polluted sea water affects the pluteus formation in various sea urchins. Especially, Heslinga (1976) reports that the pluteus process appears to be very sensitive and therefore may be best suited to assess the stress by pollution in Echinometra.…”
Section: I I Considerationsmentioning
confidence: 93%
“…It has been found that echinoderm larvae develop better in 'water in which a community of north-western forms had been living ('elegans' or 'western' water) (cf. Russell, 1935) than in water obtained from inshore off Plymouth or from areas with other plankton communities (Wilson, 1951;Wilson & Armstrong, 1961).…”
Section: Environmentmentioning
confidence: 98%
“…Water quality bioassays A range of techniques were deployed at sea, and while they varied considerably in sensitivity, bioassays apparently responded to the 2 water masses in the Gerrrldrl Bighi (Becker et al 19921, diffeien:ititing the continental coastal water from the offshore water, as Wilson & Armstrong (1961) did in the English Channel. The ability to differentiate naturally occurring water masses in this way implies that sensitivity of bioassay techniques is adequate to detect significant contamination.…”
Section: Dab -Molecular and Cellular Pathologymentioning
confidence: 99%